Processed food knowledge portal - Low, Mee Peng (2012)
Processed food knowledge portal (PFKP) is concerned with delivering a suite of knowledge contents to users via the internet.However, some of the potential entrepreneurs often face the problem to get the guidance from the expert entrepreneurs who have more knowledge on processed food business.This knowledge portal site allows the members to create and share their knowledge since the portal containing three difference levels of users namely Expert Entrepreneur, Potential Entrepreneur,and Customer.The main objective for this project is to develop a knowledge portal for processed food industry.The processed food portal can assist the potential entrepreneurs in getting knowledge and can provide experts a facility to share their knowledge at forum.The portal also provides assistance in financing,training,and marketing to these potential entrepreneurs.The portal provides variety of products by category,tips,expert experiences,forum and financial assistance.Currently there is no government portal that specifically focuses on the processed food.The iterative and increment development methodology are used in developing the portal.This methodology can get the higher satisfaction from the users.The benefit of this project is to provide the communication between experts and potential entrepreneur and help the potential entrepreneur by giving them guidance and needed assistance information on their business.The users also can get the latest news and information about processed food. The project has successfully developed the portal with its features,and should be tested by various users to get their feedback on its benefits.